2020
DOI: 10.1055/s-0040-1713885
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Autonomic Dysfunction in Spinal Cord Injury: Epidemiology, Diagnosis, and Management

Abstract: Spinal cord injury (SCI) disrupts autonomic circuits and impairs synchronistic functioning of the autonomic nervous system, leading to inadequate cardiovascular regulation. Individuals with SCI, particularly at or above the sixth thoracic vertebral level (T6), often have impaired regulation of sympathetic vasoconstriction of the peripheral vasculature and the splanchnic circulation, and diminished control of heart rate and cardiac output. In addition, impaired descending sympathetic control results in changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 133 publications
0
28
0
Order By: Relevance
“…Patients with spinal cord injuries are known to have autonomic, cardiovascular, pulmonary and motor dysfunction ( Schilero et al, 2009 ; Wecht et al, 2020 ; Williams et al, 2019 ). Therapeutic intermittent hypoxia might lead to improvements in these outcome measures.…”
Section: Repetitive Intermittent Hypoxia and Beneficial Cardiovascular Outcomes In Patient Populationsmentioning
confidence: 99%
“…Patients with spinal cord injuries are known to have autonomic, cardiovascular, pulmonary and motor dysfunction ( Schilero et al, 2009 ; Wecht et al, 2020 ; Williams et al, 2019 ). Therapeutic intermittent hypoxia might lead to improvements in these outcome measures.…”
Section: Repetitive Intermittent Hypoxia and Beneficial Cardiovascular Outcomes In Patient Populationsmentioning
confidence: 99%
“…[ 121 ] Cardiovascular autonomic dysfunction in spinal cord injury: epidemiology, diagnosis, and management Wecht et al. [ 124 ] Autonomic neuromodulation New approaches for treating atrial fibrillation: focus on autonomic modulation Sohinki et al. [ 125 ] Neuromodulation for the treatment of heart rhythm disorders Waldron et al.…”
Section: Electrical Simulationmentioning
confidence: 99%
“…Clinical trials are underway evaluating SCS in recovering lower extremity, bladder, bowel, and sexual function [ 122 , 123 ]. Additionally, both transcutaneous and implanted SCS have been shown to improve autonomic cardiovascular dysfunction that occurs after SCI [ 124 ].…”
Section: Electrical Simulationmentioning
confidence: 99%
“…Whereas Mason et al [15] and Croft et al [33] described a mean HR of around 155 beats per minute, the present study reported a value of 118 beat per minute, which is associated with a much lower exercise intensity. Since some athletes with SCI may have a disturbed HR regulation [34], and in other studies often other disabled athletes were included without SCI, this comparison has to be taken with caution.…”
Section: Speed Zonesmentioning
confidence: 99%